ANALIS IS PERUBAHAN UNDANG-UNDANG NOMOR 32 TAHUN 2024 TERHADAP UNDANG-UNDANG NOMOR 5 TAHUN 1990 TENTANG KONSERVASI SUMBER DAYA ALAM HAYATI DAN EKOSISTEMNYA DARI PERSPEKTIF HUKUM PIDANA - Faiza Ramadani Abrar; Yenny Fitri Z (TAHKIM, 2025)
This study is related to the analysis of changes to Law Number 32 of 2024 against Law Number 5 of 1990 concerning Conservation of Biological Natural Resources and their Ecosystems. From this change, it can be seen the government's efforts to update regulations for the implementation of national development in the preservation of biodiversity and management of its ecosystem in Indonesia. The study aims to determine what changes are made to the regulations in Law Number 32 of 2024 against Law Number 5 of 1990 concerning Conservation of Biological Natural Resources and their Ecosystems and the analysis of changes to Law Number 32 of 2024 concerning Conservation of Biological Natural Resources and their Ecosystems associated with legal certainty. This study uses normative research, using library materials as research sources, namely Law Number 5 of 1990 and Law Number 32 of 2024 concerning Conservation of Biological Natural Resources and their Ecosystems. The results of this study found 4 articles related to criminal law, namely Article 19, Article 21, Article 33, and Article 40. Law Number 32 of 2024 concerning Conservation of Biological Natural Resources and Ecosystems has provided better legal certainty because this Law provides adjustments to developments in environmental issues and global challenges and provides space for increasing the effectiveness of the implementation of natural resource conservation in Indonesia. This study is expected to contribute to the understanding of changes in conservation regulations and their implications for the management of biological natural resources and ecosystems in the future. Keywoards: conservation, biological natural resources, ecosystems